Development of a scalable design for biofuel production from green macroalgae hydrolysates - Hayet Djelal; Alaa Salma; Walaa Sayed; Audrey Cabrol; Maud Benoit; Amance Corat; Abdeltif Amrane; Ronan Pierre (Algal Research, 2026)

Spatial association of Mycobacterium bovis infection in cattle and badgers at the pasture interface in an endemic area in France - Malika Bouchez-Zacria; Ariane Payne; Sébastien Girard; Céline Richomme; Maria-Laura Boschiroli; Maud Marsot; Benoit Durand; Stéphanie Desvaux (Preventive Veterinary Medicine, 2023)

“BACACIX”, a spatial index combining proxies of bovine and badger space use associated with extended Mycobacterium bovis circulation in France - Maud Marsot; Célia Bernard; Ariane Payne; Sophie Rossi; Sandrine Ruette; Stéphanie Desvaux; Céline Richomme; Malika Bouchez-Zacria; Benoit Durand (Preventive Veterinary Medicine, 2023)

Joint species distributions reveal the combined effects of host plants, abiotic factors and species competition as drivers of species abundances in fruit flies - Benoit Facon; Abir Hafsi; Maud Charlery de la Masselière; Stéphane Robin; François Massol; Maxime Dubart; Julien Chiquet; Enric Frago; Frédéric Chiroleu; Pierre‐François Duyck; Virginie Ravigné (Ecology Letters, 2021)
The relative importance of ecological factors and species interactions for shaping species distributions is still debated. The realised niches of eight sympatric tephritid fruit flies were inferred from field abundance data using joint species distribution modelling and network inference, on the whole community and separately on three host plant groups. These estimates were then confronted the fundamental niches of seven fly species estimated through laboratory‐measured fitnesses on host plants. Species abundances depended on host plants, followed by climatic factors, with a dose of competition between species sharing host plants. The relative importance of these factors mildly changed among the three host plant groups. Despite overlapping fundamental niches, specialists and generalists had almost distinct realised niches, with possible competitive exclusion of generalists by specialists on Cucurbitaceae. They had different assembly rules: Specialists were mainly influenced by their adaptation to host plants, while generalist abundances varied regardless of their fundamental host use.